PENGARUH KECERDASAN INTELEKTUAL, EMOSIONAL DAN SPIRITUAL TERHADAP PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN - Heri Kurnia (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study aims to find out: 1). the effect of intellectual intelligence on learning achievement in Civic Education, 2). the effect of emotional intelligence on learning achievements in Civic Education, 3). the influence of spiritual intelligence on learning achievements in Civic Education and 4). the effect of simultaneous intellectual, emotional and spiritual intelligence on the learning achievement of Citizenship Education. The population of this study was all students of State Senior High Schools in the City of Yogyakarta 2016/2017 academic year consisting of 11 State Senior High Schools with a total of 8073 students. Determination of the sample is done by simple random sampling technique . Of the 11 Public High Schools in the City of Yogyakarta, 367 students were sampled, with the provisions that each associated State High School sampled were class X students and class XI students. Data on intellectual intelligence and learning achievements in Civic Education were obtained from documents, data on emotional intelligence and spiritual intelligence were obtained through questionnaires. Data analysis techniques used to test hypotheses are simple regression and multiple linear regression. The results of the study were concluded 1). there is a positive and significant influence of intellectual intelligence on the learning achievement of Citizenship Education, with sig. (P) equal to 0,000 <0.05 regression equation of 0.119. 2). There is a positive but insignificant influence of emotional intelligence on the learning achievement of Citizenship Education, with sig. (P) of 0.119> 0.05 regression equation of -0.064. 3). There is a positive but insignificant influence of spiritual intelligence on the learning achievement of Citizenship Education, with sig. (P) of 0.365> 0.05 regression equations of 0.040. 4). There is a positive and significant influence of intellectual, emotional and spiritual intelligence on the learning achievement of Citizenship Education, with sig. (P) 0,000 <0.05. The magnitude of the coefficient of determination (adjusted R2) = 0.051 means simultaneously independent variables affect the dependent variable of 5.1% for the remaining 94.9% is influenced by variables that are not included in this study.